Ursinus, die opsteller van die Heidelbergse Kategismus, Olevianus en die Heidelbergse teologie - Steenkamp, J. J. (Hervormde teologiese studies, 1989)
Ursinus, composer of the Heidelberg Catechism, Olevianus and the Heidelberg theology Apart from a survey of the history of the Reformation in Heidelberg and the introduction of Calvinism to the Palatinate, this article concentrates on the contribution of Ursinus and Olevianus to the founding of the socalled Heidelberg theology. The Heidelberg Catechism may be regarded as a summary of the Heidelberg theology. The covenant theology of Ursinus and Olevianus provides the starting point of the Foederaltheologie of la te r times. As such it represents a bridge between Calvin and the subsequent calvinistic scholastics, but without providing any of the philosophical-speculative premises which are characteristic of the scholastics.